Ownership Structure on Companies Financial Leverage Decision: Evidence from Indonesia - Mohammad Fathon Pramuka; Toshihiko Sasaki (Faculty of Economics and Business Universitas Jenderal Soedirman, 2021)
The ownership structure in a firm is considered as crucial instrument for alleviating agency problems (Sun, Ding, Guo, and Li, 2017). The wider the ownership, the longer decision might be taken. The purposes of this study are to analyze the effect of ownership structure, namely managerial ownership and institutional ownership, stock market liquidity, and profitability on financial leverage. This research was conducted for 4 years from the period of 2014 to 2018. This study used 14 companies as samples. Based on the results of research and data analysis it is shown that: (1) Managerial Share Ownership has a negative effect on financial leverage, (2) Profitability (MSO) has a negative effect on financial leverage, (3) Share Turnover (MSO) has no effect on financial leverage, (4) IO has a negative effect on financial leverage, (5) Profitability (IO) has a positive effect on financial leverage, (6) Share Turnover (IO) has no effect on financial leverage. The implications of the results above are as follows: theoretically, this research provides insight into the implementation of agency theory in funding decisions. Because this research was carried out in manufacturing companies listed in LQ45, highlight the generalization of theories in all contexts, especially in developing countries such as Indonesia. At a practical level, this result can be used by investors, fund managers as a reference in making funding decisions, whether to prioritize internal or external funding.